Calculati aria unui patrat care are perimetrul de 7,2 cm

Answers

Answer 1
Answer:

A=l^2=\left((P)/(4)\right)^2=\left((7,2)/(4)\right)^2=1,8^2=3.24\;cm^2.

Green eyes.


Related Questions

Tough Math Help !Use PRT To Solve ( Time in Year) P=300$ R=0.9 T=4 months * 4 months change to a reduced fraction. there are 12 months in one year. Find I
Four children have small toys. The first child has 1/10 of the toys, the second child has 12 more toys than the first, the third child has one more toy of what the first child has and the fourth child has double the third child. How many toys are there?
Roman has a certain amount of money. If he spends $15, then he has 1/4 of the original amount left. How much money did Roman have originally?Bly 13 x
The 162-room BeeGee Hotel, located just outside Philadelphia, Pennsylvania, requires room attendants to clean 18 rooms per day. If the hotel is forecasting a full house next Monday, how many guest room attendants will be needed to cover the day's cleaning tasks?
What basic trigonometric identity would you use to verify that csc x sec x cot x= csc^2x.

What would a model be for the math word problem Sammy has 50 pieces of gum. He wants to give 1/2 of the pieces to his brother and 3/4 of the pieces to his sister.

Answers

Answer: X = 1/2(y)

Z= 3/4(x)

But x= 1/2(y)

So z = 3/4 * 1/2(y)

Z = 3/8(y)

Total= 1/2(y) +3/8(y) + 1/8(y)

Step-by-step explanation:

two men start from 2 places 600km apart and travel towards each other, the first travelling 5km/h faster than the other. they meet after 8 hours. what is the speed of the fastest man? I know that this relates to the following formula; speed = distance/time, but don't understand how to resolve correctly

Answers

If they meet after 8 hours, then the sum of their average speeds is 600/8=75 km per hour.  If one is 5 km per hour faster than the other, then if we set the speed of the slower man to x, we have:

2x+5=75

So:

2x=70

x=30

The fastest man is 5 km per hour faster than the slower, so he travels 35 km per hour.

Joe will go to the swimming pool on 20 different days this month. • a one-day pass to the pool is $2.25. • a monthly pass to the pool is $30.00. how much money will joe save by buying a monthly pass

Answers

Joe will save 20 dollars buying a monthly pass

Concorde could travel 1 mile every 3 seconds.
How many miles per hour (mph) is that?

Answers

Concorde could travel distance of 1 mile every 3 seconds which is equals to 1200 miles per hour.

What is distance?

" Distance is defined as the path travelled between two points."

Conversion used

1miunte = 60 seconds

1 hour = 60minutes

          = 60 × 60 seconds

          = 3600 seconds

According to the question,

Distance travelled in 3 seconds = 1mile

Distance travelled 1 second = (1)/(3) mile

Distance travelled in 1hour  =  (3600)/(3)

                                              = 1200 miles per hour (mph)

Hence, Concorde could travel distance of 1 mile every 3 seconds which is equals to 1200 miles per hour.

Learn more about distance here

brainly.com/question/15172156

#SPJ3

total seconds =60*60=3600
dividing by 3 we get, 1200

so its 1200 mph

Find the non-extraneous solutions of the square root of the quantity x plus 9 minus 5 equals quantity x plus 4

Answers

Answer:

x=8 and x=9

Step-by-step explanation:

The given equation is:

√(x+9)-5=x+4

On solving this equation, we get

√(x+9)=x+9

Squaring on both sides, we get

x+9=x^2+81+18x

x^2+18x-x-9+81=0

x^2+17x+72=0

x^2+8x+9x+72=0

(x+8)(x+9)=0

Thus, the solution of the above equations are x= 8 and x=9.

I"m guessing you mean
√(x+9) -5=x+4
add 5 to both sides
√(x+9)=x+9
square both sides
x+9=x²+18x+81
minus x+9 both sides
0=x²+17x+72
factor
what 2 numbres multiply to get 72 and add to get 17?
8 and 9
0=(x+8)(x+9)
set to zer

0=x+8
x=-8

x+9=0
x=-9

test each

√(-8+9) -5=-8+4
√(1) -5=-4
1-5=-4
-4=-4
true

√(-9+9) -5=-9+4
√(0) -5=-5
-5=-5
true


the solutions are x=-9 and -8

X+3y=3
2x-4y=6

solve the equations

Answers

Subtract the second equation from double the first equation:

2x+6y-2x-(-4y)=0

10y=0

Therefore, y=0.  Substituting this into the first equation, we see that:

x+3(0)=3

x=3

Therefore, x=3.  The solution to this system is x=3, y=0, or (3, 0).
so divide the second equation by 2
x-2y=3
the first equation is
x+3y=3
subsitute
3=3 so therefor
x-2y=x+3y
subtract x from both sides
-2y=3y

add 2y to both sides
0=5y
ofviously y=0 so subsitute
x-2y=3
x-(2)0=3
x-0=3
x=3

x=3
y=0